2020
DOI: 10.1111/jcpp.13268
|View full text |Cite
|
Sign up to set email alerts
|

Greater functional connectivity between sensory networks is related to symptom severity in toddlers with autism spectrum disorder

Abstract: Background Symptoms of autism spectrum disorder (ASD) emerge in the first years of life. Yet, little is known about the organization and development of functional brain networks in ASD proximally to the symptom onset. Further, the relationship between brain network connectivity and emerging ASD symptoms and overall functioning in early childhood is not well understood. Methods Resting‐state fMRI data were acquired during natural sleep from 24 young children with ASD and 23 typically developing (TD) children, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…This result from localization analysis suggests that the somatosensory network drives, at least in part, the increase in modularity across time seen in neurotypicals relative to those with ASD (Harlalka et al, 2018 ; Henry et al, 2018 ). In a recent study, it was further demonstrated in toddlers with ASD that the degree of overconnectivity between visual and sensorimotor networks was associated with greater autism symptoms, and an age-related weakening of the visual-auditory between-network connectivity was observed in the ASD but not the TD group (B. Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…This result from localization analysis suggests that the somatosensory network drives, at least in part, the increase in modularity across time seen in neurotypicals relative to those with ASD (Harlalka et al, 2018 ; Henry et al, 2018 ). In a recent study, it was further demonstrated in toddlers with ASD that the degree of overconnectivity between visual and sensorimotor networks was associated with greater autism symptoms, and an age-related weakening of the visual-auditory between-network connectivity was observed in the ASD but not the TD group (B. Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the pattern of age-related changes in spontaneous activity in the cingulate and insula was disrupted in infants with a family history of ASD (Ciarrusta et al, 2019 ). Furthermore, stronger functional connectivity and the degree of overconnectivity between visual and sensorimotor networks were associated with greater autism symptoms in toddlers (B. Chen et al, 2020 ; Ciarrusta et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations